Chart Image from Observatory in School Cognitive Linguistic - Nwzad Anwer Omer; Shno Aula Hamadamin (QALAAI ZANIST JOURNAL, 2023)
One of the modern schools of now days is cognitive linguistic school which is a scientific Multidimensional and social school, dependence in body experiences of human. Contains different methods of languages and other sciences. One of these schools that importance for meaning. One of the characteristics of working in this school is emphasizing meaning .What is seeing in this school in delivering the messages some completed theories in school is working, some of them are in morphology level & syntactic and some of them are in semantic level & pragmatic. The school is Not importance for separate semantic and pragmatic levels their is no Border Discrimination between them. The school depends on human scenes ,a picture which is delivering the message .in Cognitive school some types of pictures are selecting which is different from other schools .Three types of pictures are: scheme image, mind image, coding image. The aim of research is emphasizing scheme image.